Qanun Jinayat from the Perspective of the Legal System: A Study of Understanding, Acceptance, and Implementation in Aceh - Mutia, Isna; Bin Ahmad, Khadher; Binti Che Omar, Siti Azwanie; Zehan Saari, Nur Faizatul; Bahri, Samsul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to analyze the understanding, acceptance, and implementation of the qanun jinayat, especially 'uqūbāt ta'zir, in the Banda Aceh community. Using mixed methods, analyzed using legal sociology, especially Friedman's legal system theory. Quantitative data were collected from 300 respondents through systematic sampling (Krejcie and Morgan formula) and analyzed descriptively using SPSS 21.0. Qualitative data were obtained through in-depth interviews with officials of the Islamic Sharia Office of Banda Aceh City and Aceh Province, as well as expert interviews with Islamic law academics. The results of the study indicate an imbalance between its elements, namely the legal culture is relatively strong, indicated by a moderate level of understanding (52%) but has a very high level of acceptance of 'uqūbāt ta'zir (90%). In contrast, the legal structure is relatively weak, where 53% of respondents considered the implementation of 'uqūbāt ta'zir to be imperfect and 48.7% expressed dissatisfaction with the government's performance. Therefore, the enforcement of 'uqūbāt ta'zir requires institutional strengthening and continuous capacity building of law enforcement officials. Although Aceh's legal culture surrounding 'uqūbat ta'zir demonstrates strong normative acceptance alongside moderate legal understanding, its legal structure remains weak, suggesting that institutional reforms must prioritize capacity, consistency, and accountability over mere norm dissemination. This study offers concrete steps to implement the Qanun Jinayat within the framework of the Unitary State of the Republic of Indonesia. Synchronization of central and regional laws and collective political policy support from all stakeholders are required so that implementation can run well and be beneficial for the people of Aceh as a whole.